2014
DOI: 10.9790/3021-04451821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drip Irrigation Levels on Yield of Salad Cucumber under Naturally Ventilated Polyhouse

Abstract: An experiment was conducted to study the yield response of salad cucumber under different drip irrigation levels to determine the most suitable irrigation requirement for salad cucumber grown under naturally ventilated polyhouse. Drip irrigation applied at the rate of 2 litre plant-1 day-1 to the control plants was reduced by 5, 20, 35 and 50% by applying corresponding irrigation rates of 1.9, 1.6, 1.3 and 1 litre plant-1 day-1 under different treatments. Lowering irrigation level to 65% sustained the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The highest WUE, 13.45 and 13.66 kg/ha/mm in 2018 and 2019, respectively, was obtained from the combination of twice-weekly water application with mulching and fertilizer (I4MF) while the lowest was from four-times weekly watering with mulching and fertilizer (I4MF), for both seasons. Some researchers have also reported maximal WUE values for cucumber under reduced irrigation conditions (Abdul Hakkim & Jisha Chand, 2014;Hashem, Medany, Abd El-Moniem, & Abdallah, 2011;Kirnak & Demirtas, 2006). The results from the present study also confirmed that water productivity under a mulching/-water-saving strategy was higher under lower irrigation (I4) than with full or excess water application.…”
Section: Wue Nue and Yieldsupporting
confidence: 88%
“…The highest WUE, 13.45 and 13.66 kg/ha/mm in 2018 and 2019, respectively, was obtained from the combination of twice-weekly water application with mulching and fertilizer (I4MF) while the lowest was from four-times weekly watering with mulching and fertilizer (I4MF), for both seasons. Some researchers have also reported maximal WUE values for cucumber under reduced irrigation conditions (Abdul Hakkim & Jisha Chand, 2014;Hashem, Medany, Abd El-Moniem, & Abdallah, 2011;Kirnak & Demirtas, 2006). The results from the present study also confirmed that water productivity under a mulching/-water-saving strategy was higher under lower irrigation (I4) than with full or excess water application.…”
Section: Wue Nue and Yieldsupporting
confidence: 88%
“…This enhanced the vegetative growth of cucumber and almost doubled its productivity compared to the surface furrow irrigation (SFI) (Yaghi et al, 2013). According to Hakkim and Chand (2014), the total quantity of water applied through 65% drip irrigation level showed 35% water saving over control with highest WUE (6148.31 kg ha -1 cm -1 ).…”
Section: Deficit Irrigationmentioning
confidence: 99%
“…Hakkim and Chand (2014), has mentioned a benefit cost (BC) ratio of 3.41 in cucumber production in a naturally ventilated greenhouse.…”
Section: Economic Analysismentioning
confidence: 99%
“…The author concluded that the proper amount of water application boosts the vigorous growth of cucumber, which eventually increases the number of fruit per plant. In a similar way, Hakkim and Chand [2014] recorded . Biometrical and biochemical properties of fruits of mini cucumber plants grown under various irrigation regimes in an unheated greenhouse.…”
Section: Discussionmentioning
confidence: 79%